Reconstruction of bilateral ramus-condyle unit defect using custom titanium prosthesis with preservation of both condyles. (December 2021) - Farajpour, Hekmat; Bastami, Farshid; Bohlouli, Mahboubeh; Khojasteh, Arash
Abstract: Background: Novel technologies for management and reconstruction of complex bony defects regarding both function and facial appearance are interestingly used in maxillofacial surgery. In the current study, we demonstrated reconstruction of a bilateral ramus-condyle unit (RCU) defect while preserving both condyles by a novel designed titanium prosthesis using virtual surgical planning (VSP), computer-aided design and manufacturing (CAD/CAM), and Selective Laser Melting (SLM) technologies. Materials and methods: A 3D customized titanium prosthesis was designed for a 49 -year-old patient with bilateral mandibular aggressive central giant cell granuloma (CGCG) according to mandibular normal anatomy and structure while preserving bilateral intact condyles. Finite element study was performed to investigate the effects of new design strength and the stress shielding phenomenon. The design of macro-pores inside the body of prosthesis allowed it to act as a scaffold for bone tissue engineering under load bearing conditions. Results: Analysis of the strength and stress shielding phenomenon demonstrated favorable outcomes regarding the novel design. For instance, there was no stress shielding in any of the preserved condyles with regard to the size and distribution of stresses. Also, the stress distribution around the pores showed that these pores had no effect on the strength of the prosthesis. Thirty month follow-ups after reconstruction of bilateral RCU defect showed normal jaw function with a favorable facial appearance and mandibular contour. Conclusion: We design a novel patient-specific prosthesis with desirable biomechanical features for reconstruction of bilateral RCU defect after resection of the benign tumor with preservation of bilateral intact condyles.